Contactless Measurement of Vital Signs with Radar Sensors - Pele Anne Francoise (Ee Times Europe, 2023)
Special Report: Embedded World, Cutting CO2 Emissions with Renewable Energy, Room-Temperature Quantum Computing, Semiconductor Startup Investments Topped $38B in 2022, Environmental Sustainability with Modular SDRs.